Funding of protected areas: A pure public task? Case studies from Austria. - Withalm, Grazia (TU Wien, 2017)
Protected areas (PA) are nowadays established and managed increasingly by local nonprofit organisations, local or regional stakeholders. The public sector, however, is still seen as the main responsible for PA funding according to literature. The reason therefore is that on a first glance the goods and services produced by PAs are defined as (impure) public goods. On a second glance, however, PAs provide a lot of different services, which have very diverse characteristics, and thus can not only be defined as public goods but can be classified also as club goods, private goods or common pool resources (commons). Consequently, the question arises if there is a mismatch of public and private funding. The aim of this study is, thus, first to analyse the international and national (Austria) situation of PA funding. Second, an empirical analysis aims at investigating the sources of PA funding and their accordance to a "publicness" indicator of PAs. This indicator has been developed on the basis of the ecosystem goods and services provided by the respective PAs. The results show, on the one hand, that PA funding is a public task according to the public goods theory. On the other hand, the empirical analysis shows a little mismatch of public and private funding. An increased expenditure of civil society and private companies could contribute, hence, to a generally more sustainable funding for PAs.
Keywords: Naturschutz; Schutzgebiet; Finanzierung; Öffentliche Güter; Öffentliche Aufgabe; Fallstudie; Förderpolitik